Long-term results after non-operative and operative treatment of radial neck fractures in adults - Keil, Holger; Schnetzke, Marc; Vetter, Sven Y.; Beisemann, Nils; Swartman, Benedict; Grützner, Paul Alfred; Franke, Jochen (Journal of orthopaedic surgery and research, 2018)
The aim of this study is to determine the functional long-term outcome after non-operative and operative treatment of radial neck fractures in adults.